A Cellular Automata Bioinspired Algorithm Designing Data Trees in Wireless Sensor Networks. (7th June 2015) - Tsompanas, Michail-Antisthenis I.; Mayne, Richard; Sirakoulis, Georgios Ch.; Adamatzky, Andrew I.
Several studies present methods to economize energy in wireless sensor networks (WSNs) which is one of the most confining resources in these systems. This paper presents a bioinspired, cellular automata (CA) based model for constructing data trees that connect all nodes with a sink node. Nonetheless, the proposed model takes into consideration not only the proximity between two nodes but also their remaining available energy. Consequently, by avoiding nodes with nearly depleted energy sources, the life time of the network can be prolonged. The plasmodium of Physarum polycephalum is the inspiration for the proposed model, as it has proved its robustness in graphically expressed problems. Moreover, CAs are able to encapsulate the parallel dynamics of the model and, thus, achieve a very fast execution.